2014
DOI: 10.7567/apex.7.062102
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of nonpolar ZnO and n-ZnO/i-ZnO/p-GaN heterostructure on Si(001) for ultraviolet light emitting diodes

Abstract: Nonpolar a-plane ZnO-film and n-ZnO/i-ZnO/p-GaN heterostructure LEDs were grown epitaxially by pulsed laser deposition and metal–organic chemical vapor deposition on Si(001) using AlN and MnS as buffer layers. X-ray diffraction pole figures showed an epitaxial relationship of ZnO() ∥ AlN() ∥ MnS(001) ∥ Si(001). A near band-edge emission from ZnO was observed at 378 nm in photoluminescence measurements. Electroluminescence of nonpolar n-ZnO/i-ZnO/p-GaN LEDs displayed UV emission at 390 nm under forward and reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…17) To solve these issues, we have proposed nonpolar AlN film growth on a Si (100) substrate by inserting a MnS buffer layer as a template substrate for nonpolar GaN growth. [18][19][20][21][22][23][24][25][26] In terms of the lattice mismatch, the lattice constant of the a-axis of MnS (5.22 Å) is close to that of Si and 3 times that of the a-axis of AlN. In our previous study, a nonpolar AlN film on a Si (100) substrate with a MnS buffer layer was achieved by pulsed laser deposition.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…17) To solve these issues, we have proposed nonpolar AlN film growth on a Si (100) substrate by inserting a MnS buffer layer as a template substrate for nonpolar GaN growth. [18][19][20][21][22][23][24][25][26] In terms of the lattice mismatch, the lattice constant of the a-axis of MnS (5.22 Å) is close to that of Si and 3 times that of the a-axis of AlN. In our previous study, a nonpolar AlN film on a Si (100) substrate with a MnS buffer layer was achieved by pulsed laser deposition.…”
Section: Introductionmentioning
confidence: 95%
“…In our previous study, a nonpolar AlN film on a Si (100) substrate with a MnS buffer layer was achieved by pulsed laser deposition. [18][19][20][21][22][23] In order to realize nonpolar GaN growth on a large-diameter Si (100) substrate, we started to fabricate AlN/MnS/Si (100) structures by sputtering. 24) However, film growth of nonpolar AlN could not be achieved by sputtering owing to the instability of the MnS/Si and MnS/AlN interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the above, our group has proposed a nonpolar AlN template on a Si (100) substrate with the insertion of a MnS (100) buffer layer as a template substrate for nonpolar GaN growth. [25][26][27][28][29][30][31][32][33] MnS has two properties that make it suitable as a substrate for nonpolar AlN growth. Firstly, the interfaces between the MnS and Si layers and between the AlN and MnS will be sharp because the sulfide will not react with the Si or the nitride.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MnS has the same cubic structure as Si, and the a axis lattice constant of MnS is 0.522 nm, which is close to √3 times the a axis lengths for AlN and Si (100). Using an MnS buffer layer, nonpolar AlN film growth on a Si (100) substrate has been demonstrated by pulsed laser deposition, [25][26][27][28][29][30] although it would be preferable to use sputtering to realize nonpolar GaN growth on a large diameter Si (100) substrate. As an example, Tatejima et al reported the fabrication of AlN/MnS/Si (100) structures by sputtering 31) but did not obtain single phase nonpolar AlN, and found that the crystallinity of the nonpolar AlN was insufficient for use as a GaN substrate.…”
Section: Introductionmentioning
confidence: 99%
“…A s wide-direct-bandgap II-VI semiconductors, ZnSe and ZnO have important applications in various optoelectronic devices, such as photodetectors, lightemitting diodes (LEDs), laser diodes (LDs), and solar cells. [1][2][3][4] For ZnSe, a moderate bandgap of ∼2.7 eV at room temperature makes it suitable to absorb light from ultraviolet to blue. On the other hand, ZnO with a bandgap of ∼3.37 eV at room temperature could absorb ultraviolet light effectively and has received significant attention for fabricating different heterostructures with enhanced device performance in photovoltaics, photodetectors, LEDs, and so forth.…”
mentioning
confidence: 99%